Engaging Chicago Residents in Climate Change Action: Results from Rapid Ethnographic Inquiry - Lynne M. Westphal; Jennifer L. Hirsch (Cities and the Environment, 2010)
Addressing climate change requires action at all levels of society, from neighborhood to international levels. Using Rapid Ethnography rooted in Asset Based Community Development theory, we investigated climate-friendly attitudes and behaviors in two Chicago neighborhoods in order to assist the City with implementation of its Climate Action Plan. Our research suggests a means to effectively engage urban residents at the household and neighborhood level: understand the issues of importance in each neighborhood, assess the ways these are related to climate change mitigation or adaptation actions, and engage residents from this perspective, meeting mutually compatible goals. This builds upon the concept of co-benefits, but puts the neighborhood concerns rather than climate change issues in the lead in order to meet multiple goals. Rapid ethnography is a method well-suited to develop these understandings. It allows quick but in-depth insights into the attitudes, behaviors, goals, and aspirations of a neighborhood or other groups of people.